Analisis Pengaruh Portofolio Kredit Terhadap Kualitas Kredit dan Profitabilitas pada BPR Konvensional di Riau - Febrina, Dian (Jurnal Daya Saing, 2017)
Abstract: The present research was conducted at Riau Province. The purpose of this research is to influence of credit portfolio to non perfoming loan (NPL) and profitability (ROA) in Bank Perkreditan Rakyat (BPR) Convensional in Riau. The population of this research is a Bank Perkreditan Rakyat Convensional from annual report are listed in Perbarindo Riau during 2009-2013 with the number of saturation samples are 33 BPR in Riau. This research apply on using portofolio credit based on a type of used that is working capital loan, investment loan and consumer loan as an exogenous variable, credit quality (NPL) as an intervening variable and profitability (ROA) as a endogenous variable. The data were analyzed using path analysis. The result of this study indicate that working capital loan through credit quality indirectly significant negative effect on profitability, but the working capital loan directly positive effect on profitability. While investmen loan and consumer loan positive impact on profitability either directly or indirectly throught credit quality. Finally, credit quality and negative significant effect on profitability. Keywords: credit portfolio, working capital loan, investment loan, consumer loan, credit quality, non performing loan (NPL), profitability, return on assets (ROA) and path analysis.